PENGARUH BELANJA DAERAH SEKTOR PARIWISATA DAN PERDAGANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN PENDAPATAN ASLI DAERAH DI KOTA BONTANG: PENGARUH BELANJA DAERAH SEKTOR PARIWISATA DAN PERDAGANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN PENDAPATAN ASLI DAERAH DI KOTA BONTANG - Silverawaty, Silverawaty; Rochaida, Eny; Juliansyah, Juliansyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the influence of regional government expenditure in the tourism and trade sectors on the non-oil and gas Gross Regional Domestic Product (non-oil GRDP) and its impact on Local Own-Source Revenue in Bontang City, both directly and indirectly. A quantitative approach employing path analysis was used to identify causal relationships among the variables. The study utilizes ten years of time-series secondary data obtained from the Central Bureau of Statistics and official regional financial documents. The findings indicate that government expenditure in the tourism sector has a positive and significant effect on the non-oil GRDP. In contrast, expenditure in the trade sector shows a positive but statistically insignificant effect on the non-oil GRDP. Furthermore, the non-oil GRDP demonstrates a positive and significant effect on Local Own-Source Revenue. The path analysis also reveals an indirect effect of tourism-sector expenditure on Local Own-Source Revenue through the non-oil GRDP, suggesting that increasing budget allocation for tourism can strengthen local economic activities and ultimately enhance regional fiscal income. Conversely, the indirect effect of trade-sector expenditure on Local Own-Source Revenue through the non-oil GRDP is not significant. Overall, these results highlight the strategic role of the tourism sector in driving regional economic performance and strengthening local fiscal capacity.